ANALISIS KOMPUTASI TEGANGAN AKIBAT UJI JATUH BEBAS DENGAN KETINGGIAN 3 METER PADA KOMPOSIT YANG DIGUNAKAN SEBAGAI PELINDUNG DADA PENGENDARA SEPEDA MOTOR - Gunawan H; M. Sabri; Ikhwansyah Isranuri; Pramio G. Sembiring; A. Husein Siregar (DINAMIS, 2017)
The goal of this research is to identify computationally the stress and force that occur in the motor bike body protector which created using composite material. This test is done using ANSYS software. Test is using explicit dynamic with the free-fall impact methods which make the speciment crashed to the anvil. From the test the impact force transmitted is 14.95 kN and with the stress 0.014952 Mpa. Average impact force that occur is 29.18 Mpa which is compared with the EN 1621-3 standarization limit which is 35 kN in order to determine if this body protector is consentient with the standard.